Developing ward social climate and sense of community within a high security forensic psychiatric service: Evaluating a sense of community and social climate intervention - Puzzo, Ignazio (The journal of forensic psychiatry & psychology, 2023)
Inpatient ward social climate and sense of community can influence the recovery and care experiences of forensic mental health patients. This research evaluated an intervention designed to improve social climate and sense of community within a high-secure psychiatric hospital in the UK. The intervention was offered across six wards: two wards received the full intervention, two received the partial intervention, and two received no intervention (control). Social climate and sense of community were measured prior to the start of the intervention 6 and 18 months into the intervention, using the Essen Climate Evaluation Schema and the Sense of Community Index-2. Changes in frequency of disruptive behaviour were also monitored across time points. Results revealed that the full and the partial intervention groups reported greater feelings of social climate than the control group. This effect was also observed across time points, with higher social climate scores in the full and partial intervention groups compared to control group at 6 and 18 months. Furthermore, social climate scorespredicted a significant reduction in frequency of incidents across time in the full intervention. These findings provide longitudinal evidence of the importance of developing ward social climate and sense of community within forensic inpatient settings.